Aquaculture in Peru: Situation, Challenges and Prospects - Euler Dolores‐Salinas; Lluís Miret‐Pastor (Aquaculture, Fish and Fisheries, 2025)
ABSTRACT Aquaculture in Peru is a sector with significant growth and development in recent years. However, it faces multiple challenges to ensure its sustainability. This study aims to characterize the Peruvian aquaculture system by analysing the public, private and educational stakeholders involved, as well as the productive, commercial and environmental challenges it encounters. A descriptive methodology was employed, utilizing quantitative data from secondary sources provided by public and private entities. The data reveal a substantial increase in the production and export of aquaculture products since the 1990s, peaking in 2019. However, since then, a decline in production and notable changes in export markets have been observed. This study identifies the key challenges facing Peruvian aquaculture and proposes a series of measures to ensure its sustainability.